Age-related decline in antibiotic prescribing for uncomplicated respiratory tract infections in primary care in England following the introduction of a national financial incentive (the Quality Premium) for health commissioners to reduce use of antibiotics in the community: an interrupted time series analysis. (28th June 2018) - Bou-Antoun, Sabine; Costelloe, Ceire; Honeyford, Kate; Mazidi, Mahsa; Hayhoe, Benedict W J; Holmes, Alison; Johnson, Alan P; Aylin, Paul
Abstract: Objectives: To assess the impact of the 2015/16 NHS England Quality Premium (which provided a financial incentive for Clinical Commissioning Groups to reduce antibiotic prescribing in primary care) on antibiotic prescribing by General Practitioners (GPs) for respiratory tract infections (RTIs). Methods: Interrupted time series analysis using monthly patient-level consultation and prescribing data obtained from the Clinical Practice Research Datalink (CPRD) between April 2011 and March 2017. The study population comprised patients consulting a GP who were diagnosed with an RTI. We assessed the rate of antibiotic prescribing in patients (both aggregate and stratified by age) with a recorded diagnosis of uncomplicated RTI, before and after the implementation of the Quality Premium. Results: Prescribing rates decreased over the 6 year study period, with evident seasonality. Notably, there was a 3% drop in the rate of antibiotic prescribing (equating to 14.65 prescriptions per 1000 RTI consultations) ( P < 0.05) in April 2015, coinciding with the introduction of the Quality Premium. This reduction was sustained, such that after 2 years there was a 3% decrease in prescribing relative to that expected had the pre-intervention trend continued. There was also a concurrent 2% relative reduction in the rate of broad-spectrum antibiotic prescribing. Antibiotic prescribing for RTIs diagnosed in children showed the greatest decline with a 6% relative change 2 years after the intervention. Of the RTI indications studied, the greatest reductions in antibiotic prescribing were seen for patients with sore throats. Conclusions: Community prescribing of antibiotics for RTIs significantly decreased following the introduction of the Quality Premium, with the greatest reduction seen in younger patients.